2018
DOI: 10.1002/elps.201800291
|View full text |Cite
|
Sign up to set email alerts
|

On electrophoresis of a pH‐regulated nanogel with ion partitioning effects

Abstract: The electrophoresis of a polyelectrolyte nanoparticle, whose charge condition depends on the salt concentration and pH of the suspended medium as well as the dielectric permittivity difference, is analyzed. The present nonlinear model for the electrophoresis of this pH-regulated polyelectrolyte (PE) particle is based on the consideration of full set of governing equations of fluid and ion transport coupled with the equation for electric field. The Born energy of the ions are incorporated to account for the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Since polyelectrolyte layer and bulk electrolyte solution have distinct dielectric permittivity, the self-energies of an ion, W i , in the two regions differ from each other. The difference in self-energy of the ion causes ion partitioning, which can be quantified as ion partition coefficient [44,45,46,47,48,49,50]…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Since polyelectrolyte layer and bulk electrolyte solution have distinct dielectric permittivity, the self-energies of an ion, W i , in the two regions differ from each other. The difference in self-energy of the ion causes ion partitioning, which can be quantified as ion partition coefficient [44,45,46,47,48,49,50]…”
Section: Theorymentioning
confidence: 99%
“…Ion partitioning effect modifies the charge density in polyelectrolyte layer and consequently affects the electrophoresis of soft charged particles as well as electrokinetics in soft nanochannels. Very recently, ion partitioning effect attracted a great deal of interest of researchers studying the electrophoresis of charged soft particles immersed in electrolytes [44,45,46,47,48,49,50] and electrokinetic transport in soft nanochannels [51,52,53]. The analytical and numerical studies [44,49,50,45,46,47,48],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophoresis is one of the most widely used experimental methods and practical operations for the transport, manipulation, separation, assembly, and characterization of colloidal particles. In the past, some formulas for the steady electrophoretic mobility of a charged particle were derived analytically for the cases of hard sphere (impermeable to both the solvent and small ions) , porous sphere (permeable) , soft sphere (hard in the core but porous in the surface layer) , and porous spherical shell (e.g. microcapsule or vesicle) .…”
Section: Introductionmentioning
confidence: 99%
“…From the simulational side, the electrophoretic mobility of microgels has been computed in mean‐field approximation solving numerically the electrokinetic equations . In recent particle‐based simulations that include the pH effects, we observed that the electrophoretic mobility of a coarse‐grained nanogel quickly saturates as a function of degree of dissociation .…”
Section: Introductionmentioning
confidence: 99%